THE EFFECT OF PUBLIC RELATIONS STRATEGY ON INCREASING BRAND AWARENESS THROUGH INSTAGRAM SOCIAL MEDIA - Citra Putri Devinia; Muria Putriana; Wina Puspita Sari; Asep Soegiarto; Menati Fajar Rizki (Journal of Research in Social Science and Humanities, 2024)
In the era of Industry 4.0, many people have found ways to increase brand awareness, including through their business ventures. The purpose of this research is to determine the effect of public relations strategies and social media in increasing brand awareness in restaurant businesses in South Jakarta. This research employs a quantitative research method, utilizing a probability sampling technique, namely simple random sampling, and using multiple linear regression analysis. In this study, the population consists of 13,5K social media followers, with a sample size of 100 respondents selected using the Slovin formula. This research has shown that public relations strategies and social media affect increasing brand awareness, as the content shared effectively reaches the public.Keywords: Public Relations Strategies, Social Media, Brand awareness.